2022
DOI: 10.1186/s12913-022-08440-1
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare provider and patient perspectives on access to and management of atrial fibrillation in the Northern Province, Sri Lanka: a rapid evaluation of barriers and facilitators to care

Abstract: Background Atrial fibrillation (AF) is the most common cardiac arrhythmia that affects 60 million people worldwide. Limited evidence on AF management exists from low- and middle-income countries and none from Sri Lanka. We aimed to investigate the existing AF care pathway and patients’ perception on AF management to identify barriers and enablers for optimal AF care in Northern Province, Sri Lanka. Methods A rapid evaluation was undertaken with use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…However, we know from previous research [15] that AF training is lacking in primary care units in São Paulo which can result in AF symptoms being ignored or misdiagnosed, thus depriving patients of life-saving medication. This was found in our other two project sites in Sri Lanka and China [24], confirming that poor primary care training in recognition, diagnosis and management of AF is likely a common problem in many LMICs. Avoiding stroke with anticoagulation is a key pillar of evidence-based optimal management of AF (ABC pathway) [6], but improved clinician awareness, use of clinical risk stratification [13], skills to conduct initial investigation and knowledge of treatment options by primary care staff is vital for enabling this to occur.…”
Section: Plos Onesupporting
confidence: 79%
“…However, we know from previous research [15] that AF training is lacking in primary care units in São Paulo which can result in AF symptoms being ignored or misdiagnosed, thus depriving patients of life-saving medication. This was found in our other two project sites in Sri Lanka and China [24], confirming that poor primary care training in recognition, diagnosis and management of AF is likely a common problem in many LMICs. Avoiding stroke with anticoagulation is a key pillar of evidence-based optimal management of AF (ABC pathway) [6], but improved clinician awareness, use of clinical risk stratification [13], skills to conduct initial investigation and knowledge of treatment options by primary care staff is vital for enabling this to occur.…”
Section: Plos Onesupporting
confidence: 79%
“…Another plausible reason may be due to the limited access to INR tests. Our previous research found that patients with AF must travel far distances to receive care at the Jaffna Teaching Hospital and is a barrier to optimal care (in pre-pandemic times), particularly for rural inhabitants 36 . Similar findings have been highlighted in our research in Brazil, indicating that access to INR tests is an issue in other LMICs 37 .…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted at the only tertiary hospital in the Northern Province that has cardiologists and can conduct 12-lead echocardiogram tests. Thus, most patients with AF in the province that retain AF care from government facilities, must visit Jaffna Teaching Hospital for care 36 . Our sample is therefore largely representative of all patients with AF receiving government-funded care in the region.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, given this is the first study to investigate the AF care pathway in a South Asian country and one of the few to be conducted in any LMIC, the results of our study are nonetheless a critical start to understanding how and where patients with AF go for care, what areas of the pathway need improvements and what needs to be prioritized in future AF research in LMICs.In conclusion, our findings highlight that AF diagnoses mostly occur in the A&E or inpatient department in the Northern Provence of Sri Lanka. Whilst most patients retained in care at the Jaffna Teaching Hospital (the only facility with specialist AF care)36 are on anticoagulants and rate and rhythm control medication and receive routine INR tests, early diagnosis in primary care facilities must be prioritized in Sri Lanka to provide life-saving preventative medications for reducing AF-related strokes and achieve the first step within the ABC pathway. The frequency of follow-up care visits was fewer than guideline recommendations, which in part was due to the COVID-19 pandemic but could also be due to the limited access to INR tests, a barrier 38 likely shared by other LMICs.…”
mentioning
confidence: 99%